(untitled) (Journal of the Medical College for Women & Hospital, 2024)
After transplantation, viruses are one of the most frequent sources of opportunistic infections. The particular virus encountered, the degree of immune suppression applied to avoid graft rejection, and other host characteristics influencing susceptibility all influence the likelihood of contracting a virus. Following kidney transplantation, infectious challenges have been identified as a primary source of mortality and morbidity. In order to prevent such outcome of recipient of kidney transplant, it is necessary to detect infection early and provide appropriate treatment in time. Amongst all possible infectious complications, the most common is considered to be viral infection owing to their prevalence, ability of latency and infectivity. The frequently identified virus as agents that may cause infection in case of recipients of kidney transplantation throughout the world are varicella zoster virus, herpes simplex virus, cytomegalovirus, adenovirus, Epstein-Barr virus, polyoma virus and hepatitis B. The distribution of these viruses is widespread worldwide . These microorganisms can reactivate , as these are DNA viruses, when immunosuppressive medications are given to afflicted patients. Particularly during the first six months following transplantation, these DNA viruses can result in systemic illnesses or allograft malfunction. Pretransplant evaluation, immunization, adequate prophylaxis, and preventive measures following transplant can be adopted as effective means of reducing the frequency of these viral infections. The genesis, diagnosis, prophylaxis, and management of viral infections that frequently afflict kidney transplant recipients will be covered in this review. J Med Coll Women Hosp.2024;20(1): 81-90